Proceedings of the 33rd Annual International Conference on the Design of Communication 2015
DOI: 10.1145/2775441.2775484
|View full text |Cite
|
Sign up to set email alerts
|

User-created persona

Abstract: Persona is a communicative artefact for usability that currently functions under the umbrella of User-Centred Design (UCD). Since we argue usability methods differ across cultures, this project presents a cross-cultural research probe on persona generated by indigenous Otjiherero speakers in Namibia. The objective is to find out how participants in this milieu take on, understand and portray persona artefacts, what goals of User Experience (UX) emerge from the inquiry, and whether the artefacts created simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This specific study condenses the findings presented at CaTaC by Cabrero et al [9]. The study holds persona as research foci, while it belongs to a larger project where personas are co-created with urban and rural Namibian societies from different ethnic groups, namely ovaHerero, ovaHimba, Ovambo and Khoisan [10,11,12,13,14].…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…This specific study condenses the findings presented at CaTaC by Cabrero et al [9]. The study holds persona as research foci, while it belongs to a larger project where personas are co-created with urban and rural Namibian societies from different ethnic groups, namely ovaHerero, ovaHimba, Ovambo and Khoisan [10,11,12,13,14].…”
Section: Introductionsupporting
confidence: 53%
“…This we have observed through practical studies with persona as research foci, and whereby results have shown vital differences between UCD persona as it currently is and the methods to elicit data representative of the users for whom technological products or services may eventually be aimed at [10,11,12,13,14].…”
Section: User-created Personasmentioning
confidence: 98%
See 2 more Smart Citations
“…Persona as a Tool was framed in the Global North anchored in its etymology and semiotics, thus it carries values of its context of original use. As such there are two emerging and opposing views in using persona elsewhere: deployed as is [2,10,15,18,19,22,23], and adapting it to derive further situated offerings [3,4,8,16,20,31].…”
Section: Introductionmentioning
confidence: 99%